Better Together: A Joined-Up Psychological Approach to Health, Well-Being, and Rehabilitation - Orla M. Muldoon (Frontiers Research Topics, 2016)
Health and well-being is best understood in terms of a combination of biological, psychological, and social factors. But how 'social' is the biopsychosocial model when applied to mental health and rehabilitation? Psychology has traditionally viewed health as being determined by individual behavior. An integrative psychological approach is required to draw understanding from sociology, social psychology, and politics to consider how wider systemic, structural, and contextual factors impact on health behavior and outcomes. This e-book is dedicated to examining collective and community approaches to well-being and rehabilitation. In particular, the articles contained within this e-book are seeking to understand how social integration, social groups, social identity, and social capital influence health, well-being, and rehabilitation outcomes.